Effects of white spot disease and bio-security on shrimp farming in Bangladesh - Debnath, P.P.; Karim, M.; Keus, H.J.; Mohan, C.V.; Belton, Ben (Japanese Society of Fish Pathology, 2016)
Shrimp (Penaeus monodon) culture accounts a large proportion of Bangladesh’s aquaculture industry by value, and is the country’s second largest source of export earnings. But it has encountered enormous problems due to the spread of diseases, particularly white spot disease (WSD), and has incurred significant economic losses as a result. The major factors encouraging WSD outbreaks are the production of post larvae (PL) using wild broodstock and traditional farming systems with poor farm level bio-security. Between 2005 and 2014 WorldFish tested broodstock, nauplii and PL from hatcheries in Bangladesh using polymerase chain reaction (PCR) technique, as part of a program to supply white spot syndrome virus (WSSV) free PLs to project farmers. A strong positive correlation (R = 0.743) was found among WSSV infected broodstock and WSSV infected nauplii, providing evidence of transmission of WSSV from mother to PL in hatcheries. On an average, every year almost 36.19% of hatchery produced PL was found to be WSSV positive considering positive nauplii batches from 2005 to 2014. This would be sufficient to contaminate almost the entire farming system, as 88% of farming area is under traditional farming practice. Developing commercial PCR testing facilities for ensuring supply of WSSV free seed and implementing farm level bio-security programs could reduce disease risks, improve farm productivity and contribute to country’s economy.